Pembentukan Kader Ceria (Cerdas Mencegah Anemia) Pada Remaja, Yogyakarta - Yuli Astuti; Dyah Artini; Nurpuji Mumpuni (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Anemia is a health problem that is still an important indicator of health status in society. Anemia is a condition where hemoglobin levels are less than normal (<12.5-17.0 gr/dl). Vulnerable groups who experience anemia in society are women and teenagers. Adolescents are at risk of losing iron, because in adolescents there is a growth process that requires an increased need for iron. This community service aims to create cadres to prevent anemia among teenagers. The method of implementing this service is carried out in several stages including coordination with partners, formation of Ceria cadres, cadre development, and socialization of Ceria cadres. The results of this service were that 13 Ceria Cadres underwent anemia screening and Ceria Cadre coaching. The results of the anemia screening showed that 38.46% had anemia, the majority on the pretest questionnaire had sufficient knowledge (53.85%), the posttest had good knowledge (100%) and the evaluation of hemoglobin levels after coaching was 100% normal. The conclusion is that there is an increase in knowledge and hemoglobin levels in Ceria Cadres after coaching.